2013
DOI: 10.1007/s10654-013-9827-6
|View full text |Cite
|
Sign up to set email alerts
|

Better risk assessment with glycated hemoglobin instead of cholesterol in CVD risk prediction charts

Abstract: Traditional risk charts for the prediction of cardiovascular disease (CVD) include cholesterol parameters. We evaluated how models predict fatal CVD when cholesterol is replaced by glucose parameters. We used data from NHANES III, a US survey conducted 1988-1994 (follow-up until 2006); 15,454 participants (1,716 CVD deaths) were included. Based on the ESC SCORE method, we used age, sex, blood pressure, smoking and either of the following: (1) total cholesterol, (2) total-to-HDLcholesterol, (3) glucose, (4) gly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…This includes elevation of glucose and HbA 1c in the normal range in addition to the elevation that occurs in diabetes 60, 61, 63, 64, 65. Further, observations in the general population have shown that HbA 1c and blood glucose are better markers of cardiovascular and CHD risk than either HDL cholesterol or total cholesterol66, 67 (see also Experimental section).…”
Section: Discussionmentioning
confidence: 94%
“…This includes elevation of glucose and HbA 1c in the normal range in addition to the elevation that occurs in diabetes 60, 61, 63, 64, 65. Further, observations in the general population have shown that HbA 1c and blood glucose are better markers of cardiovascular and CHD risk than either HDL cholesterol or total cholesterol66, 67 (see also Experimental section).…”
Section: Discussionmentioning
confidence: 94%
“…The threshold value of 48 mmol/mol (6.5%) is now recognised as the cut‐off point for T2DM; therefore, from our data five of the individuals would have undiagnosed diabetes and these health assessments justify an initiative (workplace or otherwise) of screening for diabetes. In addition, HbA 1c values are have been shown to be an independent risk factor for CHD and have also been proven to be better at predicting cardiovascular risk than total cholesterol in some risk prediction models …”
Section: Discussionmentioning
confidence: 99%
“…In addition, HbA1c values are have been shown to be an independent risk factor for CHD 24 and have also been proven to be better at predicting cardiovascular risk than total cholesterol in some risk prediction models. 25 Age stratification revealed a number of changes in baseline variables and predicted risk. The changes in total cholesterol concentrations in the older age groups are consistent with previous studies.…”
Section: Risk Variable Lhb Employees (N=371)mentioning
confidence: 99%
“…However, HbA1c may be a better predictor of CVD and all-cause mortality than PG, also because it can be measured and interpreted independently of fasting state (Faeh et al, 2013).…”
Section: Discussionmentioning
confidence: 99%